Triazine-based graphitic carbon nitride: a two-dimensional semiconductor - Siller-Algara, Gerardo; Severin, Nikolai; Chong, Samantha Y.; Björkman, Torbjörn; Palgrave, Robert G.; Laybourn, Andrea; Antonietti, Markus; Khimyak, Yaroslav Z.; Krasheninnikov, Arkady V.; Rabe, Jürgen P.; Kaiser, Ute; Cooper, Andrew I.; et al. (Wiley-VCH Verlag, 2014)
Graphitic carbon nitride has been predicted to be structurally analogous to carbon-only graphite, yet with an inherent bandgap. We have grown, for the first time, macroscopically large crystalline thin films of triazine-based, graphitic carbon nitride (TGCN) using an ionothermal, interfacial reaction starting with the abundant monomer dicyandiamide. The films consist of stacked, two-dimensional (2D) crystals between a few and several hundreds of atomic layers in thickness. Scanning force and transmission electron microscopy show long-range, in-plane order, while optical spectroscopy, X-ray photoelectron spectroscopy, and density functional theory calculations corroborate a direct bandgap between 1.6 and 2.0 eV. Thus TGCN is of interest for electronic devices, such as field-effect transistors and light-emitting diodes.